I-PASS Handoff Curriculum: Computer Module - Sharon Calaman; Nancy Dollase Spector; Amy J. Starmer; Jennifer K. O'Toole; April D. Allen; Lisa L. Tse; James F. Bale; Zia Bismilla; Maitreya Coffey; F. Sessions Cole; Lauren Destino; Jennifer Everhart; et al. (Association of American Medical Colleges, 2013)
Abstract The I-PASS Computer Module provides a unique platform for asynchronous, individualized learning of key elements of the I-PASS curriculum. It features embedded knowledge questions which provide an evaluation of learners' understanding of each of the major I-PASS concepts. In addition, individual subtopics may be accessed separately if one wishes to refresh knowledge of certain components of the I-PASS Curriculum. Video elements, supplemental printable documents, and test your knowledge questions are integrated into the module. In brief, we found in a detailed review of 10,740 patient admissions that a 23% reduction in medical errors and a 30% reduction in injuries due to medical errors (preventable adverse events) occurred following implementation of the I-PASS Handoff Bundle in nine academic medical centers. In direct observation of thousands of hours of resident workflow (time motion analysis) before and after implementation of the program, conducting handoffs using the I-PASS method was found to require no more time per handoff, and resident workflow throughout the shift was likewise unchanged, including no change in the amount of time spent at the computer or in direct patient care.